An Efficient Medium Access Control Protocol with Parallel Transmission for Wireless Sensor Networks - Mitsuji Matsumoto; Mohammad Arifuzzaman (Journal of Sensor and Actuator Networks, 2012)
In this paper, we present a novel low power medium access control protocol for wireless sensor networks (WSNs). The proposed protocol, EP-MAC (Efficient MAC with Parallel Transmission) achieves high energy efficiency and high packet delivery ratio under different traffic load. EP-MAC protocol is basically based on the Time Division Multiple Access (TDMA) approach. The power of Carrier Sense Multiple Access (CSMA) is used in order to offset the fundamental problems that the stand-alone TDMA method suffers from, i.e., problems such as lack of scalability, adaptability to varying situations, etc. The novel idea behind the EP-MAC is that it uses the parallel transmission concept with the TDMA link scheduling. EP-MAC uses the methods for the transmission power adjustment, i.e., uses the minimum level power necessary to reach the intended neighbor within a specified bit error rate [BER] target. This reduces energy consumption, as well as further enhances the scope of parallel transmission of the protocol. The simulation studies support the theoretical results, and validate the efficiency of our proposed EP-MAC protocol.